Environment-friendly flame-retardant medium-voltage cable and preparation method thereof
Patent Information
- Application Number
- CN202611275696.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-21
- Publication Date
- 2026-10-30
AI Technical Summary
[0009]有鉴于此,本发明的目的在于提出一种绿色环保阻燃型中压电缆及其制备方法,用以解决现有中压电缆绝缘材料存在的以下技术问题:
全生命周期绿色环保:绝缘基体具备本征可回收性,退役后可通过热压或溶剂法回收再利用,多次回收后性能保持率优异;采用竹源生物质纳米纤维为增强阻燃组分,无卤无磷,燃烧低烟低毒,大幅降低电缆全生命周期的环境负担。
Smart Images

Figure SMS_2 
Figure SMS_3 
Figure SMS_4
Abstract
Description
Technical Field
[0001] This invention relates to the field of medium-voltage power cable technology, and in particular to a green, environmentally friendly, flame-retardant medium-voltage cable and its preparation method. Background Technology
[0002] Medium-voltage power cables are core equipment in power distribution networks, and the performance of their insulation materials directly determines the cable's service life, operational reliability, and overall environmental benefits. Currently, the industry mainstream uses cross-linked polyethylene (XLPE) as the insulation matrix for medium-voltage cables, achieving excellent room-temperature mechanical and electrical insulation properties through a permanent cross-linked network. However, in practical applications, the following significant technical bottlenecks exist: Irreversible damage and short service life: XLPE is a permanently cross-linked thermosetting material. Damage such as mechanical scratches, corona erosion, electrical treeing aging, and water treeing that occur during service cannot be repaired by itself. The insulation performance is irreversibly degraded. The average service life of medium-voltage cables in China is only 30-40 years, and the operation, maintenance and replacement costs are high.
[0003] Post-retirement recycling is difficult and carries a heavy environmental burden: the permanent cross-linked network cannot be reprocessed by heating and melting. More than one million tons of waste XLPE cables are generated globally every year, and the vast majority are disposed of by landfill or incineration. This not only wastes polymer resources but also generates a large amount of pollutants, which does not meet the requirements of development.
[0004] High-temperature space charge problem is prominent: The nonpolar molecular structure of XLPE makes it difficult to capture injected charges. At an operating temperature of 70℃ and a high field strength, a large amount of space charge accumulates, and the electric field distortion rate can reach up to 27%, which can easily lead to partial discharge, electric tree expansion, and ultimately insulation breakdown.
[0005] Insufficient electromagnetic interference resistance: With the increasing electronic level of power systems, cables are susceptible to mutual inductance interference in complex electromagnetic environments, leading to current waveform distortion and voltage nonlinear deviation, which affects power supply quality. Existing anti-interference modifications are mostly achieved by adding highly conductive / magnetic fillers, but this can easily cause a surge in dielectric loss and a decrease in insulation strength. Furthermore, the fillers have poor compatibility with the interface of non-polar polyethylene, which can easily form interface defects and induce partial discharge.
[0006] Flame retardancy and performance are difficult to balance: traditional halogenated flame retardants release highly toxic dioxins when burned, and halogen-free flame retardants such as aluminum hydroxide / magnesium are usually added in amounts greater than 30 wt%, which will seriously degrade the mechanical, insulation and processing properties of the material; more importantly, a large amount of flame retardant filler will destroy the reversibility of the dynamic cross-linking network, causing the material to lose its self-healing and recyclable properties.
[0007] In existing technologies, dynamically covalently cross-linked polyethylene can achieve self-healing and recyclability, but the pure system lacks sufficient toughness and has limited space charge suppression effect. Biomass nanofibers can enhance the mechanical properties of polymers, but unmodified cellulose has poor interfacial compatibility with polyethylene, and current research has not focused on their multifunctional synergistic effects in cable insulation. To date, no solution in the industry has been able to simultaneously achieve a synergistic improvement in intrinsic self-healing, recyclability, high insulation, electromagnetic interference resistance, halogen-free flame retardancy, and excellent mechanical properties. There is a widespread technical bias that improving one property comes at the expense of others.
[0008] Therefore, based on the relevant technologies mentioned above, there is an urgent need to develop a green, environmentally friendly, flame-retardant medium-voltage cable and its preparation method. Summary of the Invention
[0009] In view of this, the purpose of this invention is to propose a green, environmentally friendly, flame-retardant medium-voltage cable and its preparation method, so as to solve the following technical problems existing in the insulation materials of current medium-voltage cables: 1. Traditional cross-linked polyethylene (XLPE) has a permanent cross-linked network, which cannot self-repair after mechanical scratches, corona discharge, electrical treeing, etc., resulting in a short service life. After decommissioning, it cannot be melted and reprocessed, making recycling difficult and imposing a heavy environmental burden, which does not meet the requirements of green and low-carbon development.
[0010] 2. Although thermoplastic polyolefin insulation materials are recyclable, their mechanical strength and insulation performance degrade significantly at high temperatures, and their creep resistance is poor, making it difficult to meet the performance requirements of medium-voltage cables for long-term high-temperature service.
[0011] 3. Traditional halogenated flame retardants pose significant environmental hazards, while high amounts of halogen-free flame retardants can significantly degrade the mechanical and electrical properties of materials, disrupt the reversibility of cross-linked networks, hinder material recycling, and fail to achieve a balance between flame retardancy, insulation, and recyclability.
[0012] To address the aforementioned technical problems, this invention provides a green, environmentally friendly, flame-retardant medium-voltage cable, comprising, from the inside out, a conductor core, a composite insulation layer, and a sheath layer. The composite insulation layer uses modified cross-linked polyethylene with dual dynamic covalent bonds as the matrix resin, compounded with maleic anhydride-modified bamboo-derived lignin cellulose nanofibers as a multifunctional reinforcing phase, and combined with a gradient particle size composite filler of modified wave-transparent fibers and magnetic nanoparticles. Through a three-layer gradient structure design, a cable insulation system is constructed that possesses intrinsic self-healing, recyclability, high insulation, electromagnetic interference resistance, and halogen-free flame-retardant properties.
[0013] A green, environmentally friendly, flame-retardant medium-voltage cable, comprising, from the inside out, a conductor core, a composite insulation layer, and a sheath layer; The composite insulation layer is prepared from the following raw materials: matrix resin, maleic anhydride modified nanofibers, composite filler, antioxidant and compatibilizer; The composite insulating layer consists of a first insulating layer, a second insulating layer, and a third insulating layer from the inside out. The matrix resin is modified cross-linked polyethylene; The maleic anhydride-modified nanofibers are maleic anhydride-modified bamboo-derived lignin cellulose nanofibers. The composite filler is composed of modified microwave-transparent fibers and magnetic nanoparticles in a mass ratio of 1:8-15. The mass ratio of the matrix resin, maleic anhydride modified nanofibers, fillers, antioxidants and compatibilizers in the composite insulation layer is 85-94:2-6:0.5-2:1-2:2-5.
[0014] Preferably, the mass ratio of the matrix resin in the first insulating layer, the second insulating layer, and the third insulating layer is 1:0.8:0.5-0.6; The average particle size of the composite filler in the first insulating layer is <100nm, the average particle size of the composite filler in the second insulating layer is 100-200nm, and the average particle size of the composite filler in the third insulating layer is >200nm. The mass ratio of antioxidants in the first, second, and third insulating layers is 1:0.5 to 1:0.4. The compatibilizer mass ratio in the first, second, and third insulating layers is 1:0.8 to 1:1.5.
[0015] Preferably, the modified crosslinked polyethylene is prepared by a Diels-Alder cycloaddition reaction of maleimide-functionalized low-density polyethylene and a bis(2-methyl-3-furanyl) disulfide crosslinking agent, and the network contains both Diels-Alder dynamic covalent bonds and disulfide dynamic covalent bonds.
[0016] Preferably, the composite filler is obtained by mixing maleic anhydride-modified bamboo-derived lignin cellulose nanofibers with an anti-electromagnetic interference filler; The average particle size of the composite filler increases along the direction from the first insulating layer to the third insulating layer.
[0017] Preferably, the maleic anhydride-modified bamboo-derived lignin cellulose nanofibers are prepared by a one-step maleic anhydride esterification process: bamboo powder and maleic anhydride are subjected to an esterification reaction at 120-140℃, and nanofibers are obtained by mechanical fibrillation. The nanofibers have a lignin retention rate of 25%-30% and a surface carboxyl content of 1.8-2.0 mmol·g. -1 The fiber diameter is 2-3 nm and the length is >1 μm.
[0018] Preferably, the maleimide-functionalized low-density polyethylene is prepared by copper-catalyzed amination: using 1,2-dichlorobenzene as solvent and 1,10-o-phenanthroline as ligand, maleimide groups are grafted onto the low-density polyethylene molecular chain under the initiation of peroxide.
[0019] Preferably, the modified transparent fiber is a quartz fiber or silicon nitride fiber that has been treated with oxygen plasma and then modified with a silane coupling agent, with a fiber diameter of 5-10 μm and an aspect ratio of 2-6. The magnetic nanoparticles are ferrite nanoparticles, prepared by a solvothermal method combined with calcination, with a particle size controlled to be 50-350 nm.
[0020] Preferably, the conductor core is a copper alloy conductor; The sheath layer is made of polyvinyl chloride or low-smoke halogen-free polyolefin material.
[0021] A method for preparing a green, environmentally friendly, flame-retardant medium-voltage cable includes the following steps: S1. Preparation of maleimide-functionalized polyethylene: Low-density polyethylene was dissolved in 1,2-dichlorobenzene, maleimide monomer, copper catalyst and 1,10-o-phenanthroline ligand were added, and then peroxide initiator was added. Catalytic amination reaction was carried out under heating conditions, and maleimide-functionalized polyethylene was obtained after purification. S2. Preparation of maleic anhydride modified bamboo lignin cellulose nanofibers: Bamboo powder and maleic anhydride were mixed at a mass ratio of 1:8-12 and esterified at 120-140℃ under normal pressure for 3-5 hours. After washing and neutralization, the product was subjected to mechanical fibrillation to obtain a water-dispersible nanofiber suspension, which was then dried for later use. S3. Preparation of gradient electromagnetic interference suppressor fillers: After treating the microwave-transparent fiber with oxygen plasma glow discharge, it is impregnated and modified in a silane coupling agent hydrolysis solution to obtain modified microwave-transparent fiber; magnetic nanoparticles of different particle sizes are prepared by solvothermal-calcination method, and after being graded according to particle size, they are mixed with modified microwave-transparent fiber to obtain three levels of electromagnetic interference suppressor fillers with small particle size, medium particle size and large particle size respectively. S4. Preparation of three-layer insulation mixture: Maleimide-functionalized polyethylene, bis(2-methyl-3-furanyl) disulfide crosslinking agent, electromagnetic interference-resistant filler with corresponding particle size, maleic anhydride-modified nanofiber, antioxidant and compatibilizer are mixed in proportion to prepare the first, second and third insulation layer mixtures respectively. S5. Multi-layer co-extrusion coating molding adopts a three-layer co-extrusion process, in which the first, second and third insulation layer mixtures are melted and extruded from the inside to the outside, and coated on the surface of the core conductor. A composite insulation layer is formed through a cross-linking reaction. S6. Sheath extrusion: The sheath material is melted and extruded to cover the composite insulation layer, and then cooled and wound to obtain the finished cable.
[0022] Preferably, the copper catalyst in step S1 is cuprous iodide, the peroxide initiator is dicumyl peroxide, and the reaction temperature is 140-160℃. In step S3, the plasma treatment vacuum degree is 25-45 Pa, the glow discharge time is 3-5 min, the silane coupling agent mass concentration is 4%-8%, and the impregnation temperature is 45-65℃. In step S5, the extrusion temperature of the first insulating layer is 220-230℃, the extrusion temperature of the second insulating layer is 200-205℃, and the extrusion temperature of the third insulating layer is 175-180℃. After extrusion, hot-press crosslinking is carried out at 120-140℃ to complete the Diels-Alder reaction and permanent crosslinking.
[0023] The modified crosslinked polyethylene provided by this invention is prepared by maleimide-functionalized low-density polyethylene and bis(2-methyl-3-furanyl) disulfide crosslinking agent via Diels-Alder cycloaddition reaction. The network contains both Diels-Alder dynamic covalent bonds and disulfide dynamic covalent bonds, supplemented by permanent crosslinking points initiated by peroxides. The permanent crosslinking network constitutes the mechanical skeleton of the material, ensuring dimensional stability, creep resistance and electrical insulation performance under normal temperature service conditions, and meeting the basic operating requirements of medium-voltage cables. The dual reversible exchange properties of Diels-Alder bonds and disulfide bonds endow the material with intrinsic self-healing ability. Under thermal stimulation, it can repair damage such as mechanical scratches, corona erosion, and electrical tree growth through bond dissociation and recombination, restore insulation strength and mechanical properties, and significantly extend the service life of the cable. At high temperatures, dynamic bonds can reversibly dissociate, causing topological rearrangement of the cross-linked network. This gives the material the ability to melt flow and be reprocessed. Decommissioned cables can be recycled and reused through hot pressing or solvent methods, solving the industry problem that traditional thermosetting XLPE cannot be recycled. The introduction of maleimide groups and thioether structures can create deep trap energy levels within the polymer, capturing injected space charges, suppressing charge migration, reducing electric field distortion, and improving the volume resistivity and breakdown reliability of the material.
[0024] The maleic anhydride-modified bamboo-derived lignin-cellulose nanofibers provided by this invention are prepared from bamboo powder via a one-step maleic anhydride esterification and mechanical fibrillation process, with a lignin retention rate of 25%-30% and a surface carboxyl content of 1.8-2.0 mmol·g. -1 The fibers have a diameter of 2-3 nm and a length of >1 μm. Their high aspect ratio nanofibers serve as rigid reinforcing units, improving the tensile strength, fracture toughness, and tear resistance of the insulation layer through physical entanglement and interfacial interaction, thus addressing the deficiency of insufficient toughness in the polyolefin matrix. The carboxyl groups and polymerizable double bonds introduced by the surface maleic anhydride esterification can covalently bond with maleimide and furan groups in the matrix, realizing the chemical bonding between nanofibers and cross-linked polyethylene matrix, solving the problem of poor interfacial compatibility between inorganic fillers and non-polar polyolefins, and avoiding local discharge caused by interfacial voids. The retained lignin components contain a large number of aromatic structures and phenolic hydroxyl groups, which can capture free radicals generated by thermo-oxidative aging, inhibit molecular chain breakage, and improve the long-term thermo-oxidative stability of the material; during combustion, lignin can be catalyzed to form char, forming a dense barrier char layer, playing a halogen-free flame retardant role and reducing the release of smoke toxins. The abundant polar groups on the surface can provide additional deep trap sites, which, combined with the trapping effect of the matrix dynamic bonds, further enhance the space charge suppression capability and reduce the electrical conductivity current.
[0025] The composite filler provided by this invention is composed of modified wave-transparent fibers and magnetic nanoparticles in a mass ratio of 1:8-15. The modified wave-transparent fibers are quartz fibers or silicon nitride fibers modified with oxygen plasma treatment and a silane coupling agent, while the magnetic nanoparticles are ferrite nanoparticles. The magnetic nanoparticles attenuate electromagnetic wave energy through hysteresis loss and natural resonance loss, while the modified wave-transparent fibers reduce electromagnetic wave interface reflection through dielectric loss and impedance matching. The combination of these two components achieves broadband electromagnetic wave absorption, significantly improving the cable's electromagnetic interference resistance and ensuring the stability of power transmission signals. The surface polarity of the microwave-transparent fiber modified by plasma and silane coupling agent is enhanced, and the interfacial bonding force with the polyolefin matrix is strengthened. It can serve as a microscale reinforcing skeleton to homogenize the electric field distribution, suppress local electric field concentration, and avoid insulation degradation caused by the introduction of fillers. Magnetic particles and transparent fibers work together to construct a dielectric-magnetic coupling loss network, which improves electromagnetic shielding effectiveness while avoiding the problem of increased dielectric loss caused by a single highly conductive filler, thus balancing electromagnetic shielding performance and electrical insulation performance.
[0026] This invention employs a three-layer gradient insulation structure. The composite insulation layer consists of a first insulation layer, a second insulation layer, and a third insulation layer, arranged sequentially from the inside out. The mass ratio of the matrix resin in the three layers is 1:0.8:0.5-0.6. The average particle size of the composite filler increases radially (inner layer <100nm, middle layer 100-200nm, outer layer >200nm), and the antioxidant and compatibilizer are simultaneously gradient-proportioned. The first insulation layer (inner layer) uses a high matrix ratio and small-particle-size filler to form a dense structure with low porosity and high cross-linking density. This structure adheres closely to the conductor surface, effectively suppressing the initiation of partial discharge at the conductor tip and reducing charge injection and interface defects. The second insulating layer (middle layer) uses a medium matrix ratio and medium particle size filler. The uniform dispersion of the filler homogenizes the overall electric field distribution, buffers the difference in dielectric constant between the inner and outer layers, reduces interface polarization loss, and absorbs mid-frequency electromagnetic interference. The third insulating layer (outer layer) uses a relatively low matrix ratio and large-particle filler. The large-particle filler can construct a multi-level electromagnetic wave reflection interface, expand the high-frequency absorption band, and improve the electromagnetic shielding and pulse energy absorption capabilities of the outer layer. At the same time, the higher filler and lignin content can improve the surface flame retardant performance and resist external environmental erosion and flame threats. The gradient additive ratio matches the filler content and processing temperature of each layer to ensure the processing fluidity and uniformity of cross-linking reaction of each layer, while strengthening the interlayer interface bonding and avoiding interlayer delamination defects.
[0027] This invention also provides a method for preparing the aforementioned green and environmentally friendly flame-retardant medium-voltage cable, including the preparation of maleimide-functionalized polyethylene, bamboo-derived nanofibers, gradient fillers, three-layer mixtures, and multi-layer co-extrusion coating and sheath extrusion processes: using 1,2-dichlorobenzene as a solvent, 1,10-o-phenanthroline as a ligand, and cuprous iodide as a catalyst, maleimide is grafted onto the polyethylene chain under the initiation of peroxide; this method can avoid the molecular chain breakage and random cross-linking side reactions that accompany traditional peroxide modification, achieve controllable grafting of maleimide groups, ensure uniform molecular weight distribution of polyethylene, and reduce molecular defects inside the insulation; Bamboo powder is directly esterified with maleic anhydride at high temperature and then mechanically fiberized, eliminating the need for a deep lignin removal process, which greatly reduces the consumption of chemical reagents and energy, while retaining the functional activity of lignin. The preparation process is green and efficient. After classifying magnetic nanoparticles by particle size, they are mixed with modified wave-transparent fibers to obtain anti-interference fillers with three particle sizes, which precisely match the functional requirements of three-layer insulation. The gradient insulation structure is formed in one step using a three-layer co-extrusion process, simultaneously completing permanent cross-linking of peroxide and dynamic cross-linking of Diels-Alder. The interlayer bonding is tight, avoiding the interface delamination problem of step-by-step molding, and the process is simple and efficient.
[0028] This invention achieves a synergistic effect between a dual dynamic crosslinked matrix and maleic anhydride-modified nanofibers, simultaneously improving mechanical, self-healing, and insulation properties. Existing technologies generally suffer from technical biases: the addition of nanofillers hinders polymer molecular chain movement, reduces the exchange efficiency of dynamic covalent bonds, leading to decreased self-healing performance, and interface defects degrade insulation performance. In this solution, the double bonds on the surface of the maleic anhydride-modified nanofibers can directly participate in the Diels-Alder crosslinking reaction, becoming part of the dynamic crosslinking network, rather than being inert fillers. Mechanically, the covalently bonded nanofibers efficiently transfer stress, increasing the material's toughness by more than 40% compared to pure dynamically cross-linked polyethylene. In terms of self-repair, the polar groups on the surface of nanofibers can reduce the activation energy of dynamic bond exchange, thereby increasing the self-repair reaction rate by about 30%. The strength repair rate after mechanical damage reaches more than 90%, and the breakdown strength repair rate after electrical damage reaches more than 85%, achieving compatibility between reinforcement and self-repair. In terms of insulation, the deep trap energy levels introduced by the two have a synergistic superposition effect, reducing the electric field distortion rate from 27% of pure XLPE to less than 5% at 70℃, and increasing the volume resistivity by more than 1 times compared with pure dynamic cross-linked polyethylene, thus breaking through the technical prejudice that "nano-reinforcement inevitably sacrifices self-repair and insulation".
[0029] In this scheme, the gradient particle size filler is matched with the three-layer structure to achieve a smooth transition of dielectric constant from the inside to the outside, avoiding polarization loss and electric field concentration at the abrupt interface. Dynamic cross-linked networks can relax the internal stress at the filler-matrix interface through bond exchange, thereby reducing interfacial micropores and defects. The interfacial compatibility of maleic anhydride nanofibers further enhances the bonding between the filler and the matrix, eliminating interfacial gaps. The synergistic effect of these three factors enables the composite insulation to achieve an electromagnetic shielding effectiveness of over 60dB while maintaining a DC breakdown strength of over 270kV / mm and an electric field distortion rate of less than 5% at 70℃, resulting in insulation performance superior to pure XLPE.
[0030] Traditional flame retardants are mostly inert additives, which not only degrade mechanical and insulation properties but also disrupt the reversibility of cross-linked networks, reducing material recyclability. In this solution, the lignin retained by the nanofibers serves as a biomass flame retardant component. During combustion, it can catalyze the formation of a dense, expanded char layer, isolating heat and oxygen. Combined with the reversible rearrangement of dynamic bonds at high temperatures, the char layer becomes more continuous and dense, increasing the limiting oxygen index to over 28% and reducing smoke emissions by over 30%, achieving halogen-free, low-smoke flame retardancy. Neither lignin nor nanofibers disrupt the reversibility of dynamic covalent bonds. After two heat recovery cycles, the material retains more than 85% of its mechanical strength and breakdown strength, achieving a synergy between environmentally friendly flame retardancy and recyclability, and avoiding the negative impact of traditional flame retardants on recycling performance.
[0031] This invention organically integrates dynamic covalent chemistry, biomass nano-reinforcement, and gradient electromagnetic functional structure, achieving reversible cross-linking and trap regulation at the molecular level, interfacial compatibility and mechanical enhancement at the micro-nano level, and functional gradient distribution at the macro level. Ultimately, the composite insulation simultaneously meets the high insulation requirements, electromagnetic compatibility requirements, long service life requirements, and environmental protection requirements of medium-voltage cables throughout their entire life cycle.
[0032] The beneficial effects of this invention are: This invention provides a green, environmentally friendly, flame-retardant medium-voltage cable and its preparation method. Compared with the prior art, this invention has the following significant advantages: Green and environmentally friendly throughout the entire life cycle: The insulation matrix is inherently recyclable and can be recycled and reused after decommissioning through hot pressing or solvent methods. It retains excellent performance after multiple recyclings. Bamboo-derived biomass nanofibers are used as the reinforcing flame-retardant component. They are halogen-free and phosphorus-free, and produce low smoke and low toxicity when burning, which greatly reduces the environmental burden of the cable throughout its entire life cycle.
[0033] Long service life and high operational reliability: The dual dynamic bonds endow the insulation material with excellent intrinsic self-healing ability, which can autonomously repair mechanical and electrical damage and significantly extend the service life of the cable; the deep trap synergistic effect effectively suppresses space charge accumulation, reduces electric field distortion at high temperatures, and ensures stable insulation performance and greatly improves operational reliability during long-term operation.
[0034] Excellent electromagnetic interference resistance: The wideband absorption system composed of transparent fiber and magnetic particles, combined with the multi-level reflection loss of the three-layer gradient structure, achieves high-efficiency electromagnetic shielding in a wide frequency range, which can effectively resist external electromagnetic interference and ensure the signal stability of medium-voltage power transmission.
[0035] Balanced improvement in mechanical and insulation properties: The covalent reinforcement of biomass nanofibers significantly improves the toughness and creep resistance of the material. At the same time, the interface compatibility design avoids insulation degradation introduced by fillers, achieving simultaneous improvement in mechanical strength, breakdown strength and volume resistivity, fully meeting the service requirements of medium-voltage cables.
[0036] The process is highly controllable and easy to promote for industrialization: It adopts copper-catalyzed amination, one-step esterification and three-layer co-extrusion process, with smooth process connection, strong parameter controllability, and can be adapted to the process conditions of existing cable production lines, and has good prospects for industrialization. Detailed Implementation
[0037] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments.
[0038] The sources and properties of some of the raw materials used in this invention are as follows: Low-density polyethylene (LDPE): Grade 2426H, melt index 2.0 g / 10 min; Maleimide, bis(2-methyl-3-furanyl) disulfide: purity > 98%; Cuprous iodide, 1,10-o-phenanthroline, dicumyl peroxide (DCP), maleic anhydride (MAH): analytical grade; 1,2-Dichlorobenzene: Analytical grade; 40-mesh bamboo powder: industrial grade; Quartz fiber / silicon nitride fiber: diameter 5-10μm, aspect ratio 2-6; Ferric chloride, ferric nitrate, melamine, and silane coupling agent KH550: analytical grade; Antioxidant 1010: Industrial grade; Compatibilizers: maleic anhydride-grafted SBS (SBS-g-MAH), maleic anhydride-grafted polypropylene (PP-g-MAH), dopamine: industrial grade; Copper alloy conductor: Brass wire, 10mm in diameter; Low-smoke halogen-free polyolefin sheathing material: industrial grade.
[0039] Example 1: In this embodiment, the CRT cable consists of a conductor core, a composite insulation layer, and a sheath layer from the inside out. The composite insulation layer raw material composition is as follows: 89.5 parts modified cross-linked polyethylene matrix, 4 parts maleic anhydride modified bamboo-derived lignin cellulose nanofibers, 1.5 parts composite filler, 1.5 parts antioxidant 1010, and 3.5 parts SBS-g-MAH compatibilizer. The mass ratio of modified wave-transparent fiber to magnetic nanoparticles in the composite filler is 1:12. The three-layer structural parameters are: first / second / third insulation layer matrix mass ratio 1:0.8:0.55; filler particle sizes are <100nm, 100-200nm, and >200nm respectively; three-layer antioxidant mass ratio 1:0.7:0.4; three-layer compatibilizer mass ratio 1:0.9:1.5; and the modified wave-transparent fiber is quartz fiber.
[0040] Complete preparation process: 1. Preparation of maleimide-functionalized polyethylene: 100 parts of LDPE were added to a reaction vessel containing 1000 parts of 1,2-dichlorobenzene, and the mixture was heated to 150°C and stirred until completely dissolved. 8 parts of maleimide, 0.3 parts of cuprous iodide, and 0.5 parts of 1,10-o-phenanthroline were added, and the mixture was stirred until homogeneous. Then, 1.2 parts of DCP initiator were added, and the mixture was kept at 150°C for 6 hours. The reaction solution was precipitated by adding excess anhydrous methanol, filtered, and then extracted with acetone using a Soxhlet extractor for 24 hours. The mixture was then dried under vacuum to constant weight to obtain maleimide-functionalized polyethylene (grafting rate 1.82 mmol / g).
[0041] 2. Preparation of maleic anhydride-modified bamboo-derived lignin-cellulose nanofibers: Bamboo powder and maleic anhydride were mixed at a mass ratio of 1:10 and esterified at 130℃ under normal pressure for 4 hours. The product was washed with deionized water, neutralized to pH 7 with 0.1 mol / L NaOH, and washed again until neutral. A 1 wt% aqueous dispersion was prepared, mechanically fiberized at 15000 rpm for 30 minutes, and then freeze-dried for later use. Product parameters: lignin retention rate 27.14%, surface carboxyl content 1.85 mmol / g, average fiber diameter 2.67 nm, and average length 1.2 μm.
[0042] 3. Preparation of gradient electromagnetic interference suppression fillers: Modified transparent fiber: Quartz fiber is placed in a plasma treatment instrument, oxygen is introduced for 12 minutes, and glow discharge is performed at a vacuum of 32 Pa for 4 minutes; it is then immersed in 6% KH550 hydrolysate at a solid-liquid ratio of 1g:25mL, soaked at 52℃ for 2 hours, washed and dried.
[0043] Magnetic nanoparticles: ferric chloride: ferric nitrate: 53% ethanol = 3g: 1g: 13g were mixed and stirred at 7 atm and 125℃ for 8 min; the pressure was reduced to 1.5 atm and the temperature was reduced to 95℃, and melamine with a mass of 2.8 times that of ferric chloride was added and stirred for 25 min; ethanol was removed by rotary evaporation, dried at 80℃ for 11 h, kept at 300℃ for 2 h, and ball-milled and sieved to obtain three particle sizes: <100nm, 100-200nm, and >200nm.
[0044] Compounding: The three particle sizes were mixed with the modified microwave-transparent fiber at a mass ratio of 12:1 at 35℃ for 7 hours to obtain the corresponding level of anti-interference filler.
[0045] 4. Preparation of three-layer insulation mixture: Weigh out the following components according to the specified ratio: maleimide-functionalized polyethylene, 8% of bis(2-methyl-3-furanyl) disulfide crosslinking agent, anti-interference filler of corresponding particle size, nanofiber, antioxidant, and compatibilizer; mix at high speed at 120℃ for 15 min, and granulate by twin-screw extrusion (temperature 160-180℃) to obtain the first, second, and third insulation layer granules, respectively.
[0046] 5. Multi-layer co-extrusion coating molding: A three-layer co-extrusion cable production line is used to extrude three layers of insulation material from the inside out, covering the copper conductor. The extrusion temperatures of the three layers are 225℃, 203℃, and 178℃, respectively. After extrusion, the material enters a 130℃ vulcanization tube and is kept at that temperature for 30 minutes, simultaneously completing Diels-Alder dynamic crosslinking and peroxide permanent crosslinking to form a composite insulation layer with a total thickness of 4.5mm.
[0047] 6. Sheath layer extrusion: Low-smoke halogen-free polyolefin material is melt-extruded to coat the insulation layer, and then water-cooled, pulled, and wound to obtain the finished cable.
[0048] Example 2: In this embodiment, the sub-cylinder cable consists of, from the inside out, a conductor core, a composite insulation layer, and a sheath layer.
[0049] The raw material ratio of the composite insulation layer is as follows: 94 parts modified cross-linked polyethylene matrix, 2 parts maleic anhydride modified bamboo-derived lignin cellulose nanofibers, 0.5 parts composite filler, 10101 parts antioxidant, and 2.5 parts PP-g-MAH compatibilizer. The mass ratio of modified microwave-transparent fiber to magnetic nanoparticles in the composite filler is 1:8. The three-layer structural parameters are: first / second / third insulation layer matrix mass ratio 1:0.8:0.5; filler particle sizes are <100nm, 100-200nm, and >200nm respectively; three-layer antioxidant mass ratio 1:0.5:0.4; three-layer compatibilizer mass ratio 1:0.8:1.5; the modified microwave-transparent fiber is silicon nitride fiber (5μm diameter, aspect ratio 2).
[0050] Complete preparation process: 1. Preparation of maleimide-functionalized polyethylene: 100 parts of LDPE were added to a reactor containing 1000 parts of 1,2-dichlorobenzene, and the mixture was heated to 140°C and stirred until completely dissolved. 5 parts of maleimide, 0.3 parts of cuprous iodide, and 0.5 parts of 1,10-o-phenanthroline were added, and the mixture was stirred evenly. Then, 0.8 parts of DCP initiator were added, and the mixture was kept at 140°C for 5 hours. The reaction solution was poured into excess anhydrous methanol to precipitate the precipitate. After filtration, the precipitate was extracted with acetone using a Soxhlet extractor for 24 hours and dried under vacuum to constant weight to obtain maleimide-functionalized polyethylene.
[0051] 2. Preparation of maleic anhydride-modified bamboo-derived lignin-cellulose nanofibers: Bamboo powder and maleic anhydride were mixed at a mass ratio of 1:8, heated to 120℃ and stirred under normal pressure for esterification for 3 hours; the product was washed with deionized water, neutralized to pH=7 with 0.1mol / L NaOH, and washed again to neutral; a 1wt% aqueous dispersion was prepared, mechanically fiberized at 15000rpm for 30min, and then freeze-dried for later use.
[0052] 3. Preparation of gradient electromagnetic interference suppression fillers: Modified transparent fiber: Silicon nitride fiber is placed in a plasma treatment instrument, oxygen is introduced for 10 minutes, and glow discharge is performed for 3 minutes under a vacuum of 25 Pa; it is then immersed in 4% KH550 hydrolysate at a solid-liquid ratio of 1g:25mL, soaked at 45℃ for 1 hour, washed and dried.
[0053] Magnetic nanoparticles: ferric chloride: ferric nitrate: 53% ethanol = 3g: 1g: 13g were mixed and stirred at 6 atm and 120℃ for 8 min; the pressure was reduced to 1.5 atm and the temperature was reduced to 95℃, and melamine with a mass of 2.8 times that of ferric chloride was added and stirred for 25 min; ethanol was removed by rotary evaporation, dried at 80℃ for 11 h, kept at 280℃ for 1.5 h, and ball-milled and sieved to obtain three particle sizes: <100nm, 100-200nm, and >200nm.
[0054] Compounding: The three particle sizes were mixed with the modified transparent fiber at a mass ratio of 8:1 at 30℃ for 4 hours to obtain the corresponding level of anti-interference filler.
[0055] 4. Preparation of three-layer insulation mixture: Weigh out the following components according to the specified ratio: maleimide-functionalized polyethylene, 8% of bis(2-methyl-3-furanyl) disulfide crosslinking agent, anti-interference filler of corresponding particle size, nanofiber, antioxidant, and compatibilizer; mix at high speed at 120℃ for 15 min, and granulate by twin-screw extrusion (temperature 160-180℃) to obtain the first, second, and third insulation layer granules, respectively.
[0056] 5. Multi-layer co-extrusion coating molding: A three-layer co-extrusion cable production line is used to extrude three layers of insulation material from the inside out, covering the copper conductor. The extrusion temperatures of the three layers are 220℃, 205℃, and 180℃, respectively. After extrusion, the material enters a 120℃ vulcanization tube and is kept at that temperature for 35 minutes, simultaneously completing Diels-Alder dynamic crosslinking and peroxide permanent crosslinking to form a composite insulation layer with a total thickness of 4.5mm.
[0057] 6. Sheath layer extrusion: Low-smoke halogen-free polyolefin material is melt-extruded to coat the insulation layer, and then water-cooled, pulled, and wound to obtain the finished cable.
[0058] Example 3: In this embodiment, the sub-cylinder cable consists of, from the inside out, a conductor core, a composite insulation layer, and a sheath layer.
[0059] The composite insulation layer raw material composition is as follows: 85 parts modified cross-linked polyethylene matrix, 6 parts maleic anhydride modified bamboo-derived lignin cellulose nanofibers, 2 parts composite filler, 2 parts antioxidant 1010, and 5 parts dopamine compatibilizer. The mass ratio of modified microwave-transparent fiber to magnetic nanoparticles in the composite filler is 1:15. Three-layer structural parameters: the mass ratio of the first / second / third insulation layer matrix is 1:0.8:0.6; the filler particle sizes are <100nm, 100-200nm, and >200nm, respectively; the mass ratio of the three-layer antioxidants is 1:1:0.4; the mass ratio of the three-layer compatibilizers is 1:1:1.5; the modified microwave-transparent fiber is quartz fiber (diameter 10μm, aspect ratio 6).
[0060] Complete preparation process: 1. Preparation of maleimide-functionalized polyethylene: 100 parts of LDPE were added to a reactor containing 1000 parts of 1,2-dichlorobenzene, and the mixture was heated to 160°C and stirred until completely dissolved. 12 parts of maleimide, 0.3 parts of cuprous iodide, and 0.5 parts of 1,10-o-phenanthroline were added, and the mixture was stirred evenly. Then, 1.5 parts of DCP initiator were added, and the mixture was kept at 160°C for 7 hours. The reaction solution was poured into excess anhydrous methanol to precipitate the precipitate. After filtration, the precipitate was extracted with acetone using a Soxhlet extractor for 24 hours and dried under vacuum to constant weight to obtain maleimide-functionalized polyethylene.
[0061] 2. Preparation of maleic anhydride-modified bamboo-derived lignin-cellulose nanofibers: Bamboo powder and maleic anhydride were mixed at a mass ratio of 1:12, heated to 140℃ and stirred under normal pressure for esterification for 5 hours; the product was washed with deionized water, neutralized to pH=7 with 0.1mol / L NaOH, and washed again to neutral; a 1wt% aqueous dispersion was prepared, mechanically fiberized at 15000rpm for 30 minutes, and then freeze-dried for later use.
[0062] 3. Preparation of gradient electromagnetic interference suppression fillers: Modified transparent fiber: Quartz fiber is placed in a plasma treatment instrument, oxygen is introduced for 15 minutes, and glow discharge is performed under a vacuum of 45 Pa for 5 minutes; it is then immersed in 8% KH550 hydrolysate at a solid-liquid ratio of 1g:25mL, soaked at 65℃ for 3 hours, washed and dried.
[0063] Magnetic nanoparticles: ferric chloride: ferric nitrate: 53% ethanol = 3g: 1g: 13g were mixed and stirred at 8 atm and 130℃ for 8 min; the pressure was reduced to 1.5 atm and the temperature was reduced to 95℃, and melamine with a mass of 2.8 times that of ferric chloride was added and stirred for 25 min; ethanol was removed by rotary evaporation, dried at 80℃ for 11 h, kept at 320℃ for 2.5 h, and ball-milled and sieved to obtain three particle sizes: <100nm, 100-200nm, and >200nm.
[0064] Compounding: The three particle sizes were mixed with the modified transparent fiber at a mass ratio of 15:1 at 40℃ for 10 hours to obtain the corresponding level of anti-interference filler.
[0065] 4. Preparation of three-layer insulation mixture: Weigh out the following components according to the specified ratio: maleimide-functionalized polyethylene, 8% of bis(2-methyl-3-furanyl) disulfide crosslinking agent, anti-interference filler of corresponding particle size, nanofiber, antioxidant, and compatibilizer; mix at high speed at 120℃ for 15 min, and granulate by twin-screw extrusion (temperature 160-180℃) to obtain the first, second, and third insulation layer granules, respectively.
[0066] 5. Multi-layer co-extrusion coating molding: A three-layer co-extrusion cable production line is used to extrude three layers of insulation material from the inside out, covering the copper conductor. The extrusion temperatures of the three layers are 230℃, 200℃, and 175℃, respectively. After extrusion, the material enters a 140℃ vulcanization tube and is kept at that temperature for 25 minutes, simultaneously completing Diels-Alder dynamic crosslinking and peroxide permanent crosslinking to form a composite insulation layer with a total thickness of 4.5mm.
[0067] 6. Sheath layer extrusion: Low-smoke halogen-free polyolefin material is melt-extruded to coat the insulation layer, and then water-cooled, pulled, and wound to obtain the finished cable.
[0068] Comparative Example 1: This comparative example uses commercially available ordinary chemically cross-linked XLPE insulation material, single-layer extruded and coated with copper conductors of the same specification, with a total insulation thickness of 4.5mm, cross-linked with peroxide at 180℃; and covered with a low-smoke halogen-free sheath of the same specification. Features: no dynamic covalent bonds, no nanofibers, no anti-interference fillers, and no three-layer gradient structure.
[0069] Comparative Example 2: This comparative example uses maleimide-functionalized polyethylene and disulfide crosslinking agent from Example 1, without adding nanofibers or anti-interference fillers, and is single-layer extruded with a total insulation thickness of 4.5 mm. The crosslinking process is the same as in Example 1; the outer sheath is of the same specification.
[0070] Features: Contains dynamic covalent bonds, no nanofibers, no anti-interference fillers, and no three-layer structure.
[0071] Comparative Example 3: The only difference between this comparative example and Example 1 is that maleic anhydride-modified bamboo-derived lignin-cellulose nanofibers are not added; the remaining raw material ratios, three-layer structure, and preparation process are completely identical. Features: Contains dynamic bonds, anti-interference fillers, three-layer structure, and no nanofiber reinforcement.
[0072] Comparative Example 4: The only difference between this comparative example and Example 1 is that no composite anti-interference filler is added; the remaining raw material ratios, three-layer structure, and preparation process are completely identical. Features: Contains dynamic bonds, nanofibers, three-layer structure, and no anti-electromagnetic interference filler.
[0073] Comparative Example 5: The only difference between this comparative example and Example 1 is that the insulation layer is produced by single-layer extrusion, all raw materials are uniformly mixed, the filler uses a single specification with an average particle size of 150nm, and the total insulation thickness remains 4.5mm; the total raw material ratio and preparation process are consistent. Features: Contains dynamic bonds, nanofibers, and anti-interference fillers, but lacks a three-layer gradient structure.
[0074] Comparative Example 6: The only difference between this comparative example and Example 1 is that the matrix uses pure LDPE permanently crosslinked with DCP, without maleimide grafting or disulfide dynamic crosslinking agent; the other raw materials, three-layer structure, and preparation process are completely identical. Features: No dynamic covalent bonds, contains nanofibers, anti-interference fillers, and a three-layer structure.
[0075] Performance testing: The products prepared in Examples 1-3 and Comparative Examples 1-6 were subjected to the following performance tests: Mechanical properties: Refer to GB / T 1040.2-2006, dumbbell-shaped specimens, tensile rate of 50 mm / min, tensile strength and elongation at break are tested, toughness is calculated by the area of the stress-strain curve integral, and the average value of 5 parallel samples in each group is taken.
[0076] DC breakdown strength: Refer to GB / T 1408.1-2016, ball-to-ball electrode, boost rate 2kV / s, test values at 25℃ and 70℃ respectively, Weibull distribution statistical characteristics breakdown field strength.
[0077] Volume resistivity: Refer to GB / T 1410-2006, the value is measured at 70℃ and 20kV / mm using a high resistance meter.
[0078] Electric field distortion rate: Space charge distribution at 70℃ and 50kV / mm was measured using the pulse electroacoustic method (PEA). The calculation formula is as follows: .
[0079] Electromagnetic shielding effectiveness: The average shielding effectiveness in the X-band (8.2-12.4GHz) was tested using the waveguide method, referring to GB / T 30141-2013.
[0080] Flame retardant performance: Limiting oxygen index refers to GB / T 2406.2-2009; smoke density rating refers to GB / T 8323.2-2008.
[0081] Mechanical repair: The specimen is scratched with a depth of 1 / 2, heat-treated at 120℃ for 12 hours, and the tensile strength is measured to calculate the strength repair rate.
[0082] Electrical repair: After 1 hour of 10kV needle tip corona aging, the breakdown strength was measured, and after 120℃ heat treatment for 12 hours, the breakdown strength repair rate was calculated.
[0083] Recycling performance: After the sample is crushed, it is hot-pressed at 140℃ and 15MPa and repeated twice. The strength and breakdown strength retention rate are then tested.
[0084] Thermo-oxidative aging performance: After thermo-oxidative aging at 135℃ for 504 hours, the tensile strength retention rate was tested.
[0085] Interfacial peel strength: Refer to GB / T 2951.19-2008 to test the peel strength between the insulation layer and the copper conductor.
[0086] Test Results and Synergistic Effect Analysis: Performance test data are shown in Tables 1-3 below: Table 1. Test results of the core performance of the insulating materials of each sample in Examples 1-3 Table 2 Test results of the core performance of the insulation materials of each sample in Comparative Examples 1-3 Table 3 Test results of the core performance of the insulation materials of each sample in Comparative Examples 4-6 Data Analysis: As shown in Tables 1-3, the toughness of the purely dynamic cross-linked matrix (Comparative Example 2) is 82.1 MJ / m. 3 Adding only anti-interference filler (Comparative Example 3) actually reduced the toughness to 75.3 MJ / m. 3 The addition of only nanofibers (Comparative Example 4) resulted in a toughness of 94.7 MJ / m. 3 The toughness of Example 1 reached 102.0 MJ / m. 3 Its core synergistic mechanism is that the double bonds on the surface of MAH-LCNF can directly participate in the Diels-Alder crosslinking reaction, becoming covalent nodes of the dynamic network rather than inert fillers; it can efficiently transfer stress through high aspect ratio nanofibers and completely eliminate interfacial void defects between fillers and matrix through interfacial covalent bonds, thereby achieving a 24.2% improvement in toughness compared to pure dynamic matrix.
[0087] In terms of insulation performance, pure XLPE (Comparative Example 1) exhibits an electric field distortion rate as high as 27% at 70℃, which is reduced to 8.5% in the pure dynamic matrix and further reduced to 5.9% after the addition of nanofibers, while Example 1 shows only 4.2%. The volume resistivity is nearly twice that of pure XLPE. The polar imide / thioether groups introduced by the dynamic bonds, together with the carboxyl groups and lignin phenolic hydroxyl groups on the nanofiber surface, construct multi-level deep trap energy levels, synergistically capturing space charge and suppressing carrier migration, thus overcoming the technical prejudice that "the introduction of fillers inevitably degrades insulation."
[0088] The shielding effectiveness of a single-layer structure and a single filler (Comparative Example 5) is only 47.9 dB, while Example 1 achieves 62.7 dB, an improvement of 30.9%, while the breakdown strength increases from 265 kV / mm to 281 kV / mm. The three-layer gradient particle size structure achieves a smooth transition of dielectric constant from the inside to the outside: the inner layer of small-diameter filler suppresses partial discharge at the conductor tip, the middle layer homogenizes the overall electric field, and the outer layer of large-diameter particles constructs a multi-level electromagnetic wave reflection interface; it achieves both broadband and efficient absorption and avoids polarization loss at abrupt interfaces, solving the problem of "high shielding accompanied by high loss and low insulation".
[0089] In addition, nanofibers promote the uniform dispersion of magnetic particles, preventing agglomeration and the formation of conductive pathways. They also introduce more dielectric loss interfaces, further enhancing electromagnetic wave absorption and achieving a simultaneous improvement in shielding effectiveness and insulation strength.
[0090] Pure XLPE has a limiting oxygen index of only 18%, making it a flammable material; the flame retardancy of the pure dynamic matrix is not significantly improved; after adding nanofibers (Comparative Example 4), the LOI increases to 26.8%, and the smoke density decreases significantly; in Example 1, the LOI reaches 28.3%, the smoke density level is only 32.4, and the strength retention rate is still 88.7% after two recyclings.
[0091] This result overcomes the technical prejudice that "flame retardant modification will destroy the dynamic network and lose recyclability": the lignin retained in MAH-LCNF is a biomass flame retardant component, which catalyzes the formation of char during combustion to form a dense barrier layer; combined with the reversible rearrangement of dynamic bonds at high temperatures, the char layer is more continuous and dense, achieving halogen-free and low-smoke flame retardancy; at the same time, neither lignin nor nanofibers destroy the dissociation-recombination characteristics of dynamic bonds, and the cross-linked network can be rebuilt after recycling, maintaining excellent performance. Compared with Comparative Example 6, which has no dynamic bonds, the latter has an LOI of only 25.7% and is completely unrecyclable, further verifying the synergistic flame retardant effect of the two.
[0092] Existing technologies generally believe that nanofillers hinder molecular chain movement, reduce dynamic bond exchange efficiency, and thus decrease self-healing performance. However, test results show that the mechanical repair rate of the pure dynamic matrix (Comparative Example 2) is 88.6%, which increases to 90.8% after the addition of nanofibers (Comparative Example 4), and further reaches 92.5% in Example 1. The electrical damage repair rate shows the same trend.
[0093] The possible mechanism is that the polar groups on the surface of MAH-LCNF can reduce the activation energy of the exchange between Diels-Alder bonds and disulfide bonds. At the same time, the capillary effect of nanofibers promotes the interfacial diffusion of molecular chains under thermal stimulation, which in turn increases the self-repair rate and repair rate simultaneously, achieving the counterintuitive effect of "mechanical enhancement and accelerated self-repair".
[0094] After thermo-oxidative aging at 135℃ for 504 hours, the strength retention rate of pure XLPE was only 72.3%, while that of pure dynamic matrix was 85.6%, and that of Example 1 was as high as 99.2%. The phenolic hydroxyl groups of lignin have the ability to capture free radicals, which can inhibit the molecular chain breakage during thermo-oxidative aging. In synergy with the network reconstruction ability of dynamic bonds, it can significantly improve long-term thermo-oxidative stability.
[0095] In terms of interfacial peel strength, Example 1 reached 7.4 N / cm, which is more than 3 times that of pure XLPE. The polar groups of nanofibers form hydrogen bonds / coordination with the metal surface, and together with the interfacial stress relaxation ability of dynamic bonds, the two work together to enhance the bonding between the insulation and conductor interface, which can effectively avoid partial discharge caused by interfacial peel during cable operation.
[0096] In summary, this invention achieves simultaneous breakthroughs in multi-dimensional performance through the synergistic effects of dual dynamic covalent networks, bamboo-derived multifunctional nanofibers, gradient anti-interference fillers, and a three-layer structure. The various technical features are not simply superimposed, but rather produce a significant synergistic effect of 1+1>2, resulting in technical effects that are difficult for those skilled in the art to predict.
[0097] Those skilled in the art should understand that the discussion of any of the above embodiments is merely exemplary and is not intended to imply that the scope of the invention is limited to these examples; within the framework of the invention, the technical features of the above embodiments or different embodiments can also be combined, the steps can be implemented in any order, and there are many other variations of the different aspects of the invention as described above, which are not provided in detail for the sake of brevity.
[0098] This invention is intended to cover all such substitutions, modifications, and variations that fall within the broad scope of the appended claims. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this invention should be included within the scope of protection of this invention.
Claims
1. A green, environmentally friendly, flame-retardant medium-voltage cable, characterized in that, From the inside out, it consists of a conductor core, a composite insulation layer, and a sheath layer. The composite insulation layer is prepared from the following raw materials: matrix resin, maleic anhydride modified nanofibers, composite filler, antioxidant and compatibilizer; The composite insulating layer consists of a first insulating layer, a second insulating layer, and a third insulating layer from the inside out. The matrix resin is modified cross-linked polyethylene; The maleic anhydride-modified nanofibers are maleic anhydride-modified bamboo-derived lignin cellulose nanofibers. The composite filler is composed of modified microwave-transparent fibers and magnetic nanoparticles in a mass ratio of 1:8-15. The mass ratio of the matrix resin, maleic anhydride modified nanofibers, fillers, antioxidants and compatibilizers in the composite insulation layer is 85-94:2-6:0.5-2:1-2:2-5.
2. The green and environmentally friendly flame-retardant medium-voltage cable according to claim 1, characterized in that, The mass ratio of the matrix resin in the first insulating layer, the second insulating layer, and the third insulating layer is 1:0.8:0.5-0.6; The average particle size of the composite filler in the first insulating layer is <100nm, the average particle size of the composite filler in the second insulating layer is 100-200nm, and the average particle size of the composite filler in the third insulating layer is >200nm. The mass ratio of antioxidants in the first, second, and third insulating layers is 1:0.5 to 1:0.
4. The compatibilizer mass ratio in the first, second, and third insulating layers is 1:0.8 to 1:1.
5.
3. The green and environmentally friendly flame-retardant medium-voltage cable according to claim 1, characterized in that, The modified crosslinked polyethylene is prepared by maleimide-functionalized low-density polyethylene and bis(2-methyl-3-furanyl) disulfide crosslinking agent via a Diels-Alder cycloaddition reaction, and the network contains both Diels-Alder dynamic covalent bonds and disulfide dynamic covalent bonds.
4. The green and environmentally friendly flame-retardant medium-voltage cable according to claim 1, characterized in that, The composite filler is obtained by mixing maleic anhydride-modified bamboo-derived lignin cellulose nanofibers with an anti-electromagnetic interference filler. The average particle size of the composite filler increases along the direction from the first insulating layer to the third insulating layer.
5. The green and environmentally friendly flame-retardant medium-voltage cable according to claim 1, characterized in that, The maleic anhydride-modified bamboo-derived lignin-cellulose nanofibers are prepared by a one-step maleic anhydride esterification process: bamboo powder and maleic anhydride are esterified at 120-140℃, and nanofibers are obtained by mechanical fibrillation. The nanofibers have a lignin retention rate of 25%-30% and a surface carboxyl content of 1.8-2.0 mmol·g. -1 The fiber diameter is 2-3 nm and the length is >1 μm.
6. The green and environmentally friendly flame-retardant medium-voltage cable according to claim 3, characterized in that, The maleimide-functionalized low-density polyethylene was prepared by copper-catalyzed amination: using 1,2-dichlorobenzene as solvent and 1,10-o-phenanthroline as ligand, maleimide groups were grafted onto the low-density polyethylene molecular chain under the initiation of peroxide.
7. The green and environmentally friendly flame-retardant medium-voltage cable according to claim 1, characterized in that, The modified transparent fiber is a quartz fiber or silicon nitride fiber that has been treated with oxygen plasma and then modified with a silane coupling agent. The fiber diameter is 5-10 μm and the aspect ratio is 2-6. The magnetic nanoparticles are ferrite nanoparticles, prepared by a solvothermal method combined with calcination, with a particle size controlled to be 50-350 nm.
8. The green and environmentally friendly flame-retardant medium-voltage cable according to claim 1, characterized in that, The conductor core is a copper alloy conductor; The sheath layer is made of polyvinyl chloride or low-smoke halogen-free polyolefin material.
9. The method for preparing the green and environmentally friendly flame-retardant medium-voltage cable according to any one of claims 1-8, characterized in that, Includes the following steps: S1. Preparation of maleimide-functionalized polyethylene: Low-density polyethylene was dissolved in 1,2-dichlorobenzene, maleimide monomer, copper catalyst and 1,10-o-phenanthroline ligand were added, and then peroxide initiator was added. Catalytic amination reaction was carried out under heating conditions, and maleimide-functionalized polyethylene was obtained after purification. S2. Preparation of maleic anhydride modified bamboo lignin cellulose nanofibers: Bamboo powder and maleic anhydride were mixed at a mass ratio of 1:8-12 and esterified at 120-140℃ under normal pressure for 3-5 hours. After washing and neutralization, the product was subjected to mechanical fibrillation to obtain a water-dispersible nanofiber suspension, which was then dried for later use. S3. Preparation of gradient electromagnetic interference suppressor fillers: After treating the microwave-transparent fiber with oxygen plasma glow discharge, it is impregnated and modified in a silane coupling agent hydrolysis solution to obtain modified microwave-transparent fiber; magnetic nanoparticles of different particle sizes are prepared by solvothermal-calcination method, and after being graded according to particle size, they are mixed with modified microwave-transparent fiber to obtain three levels of electromagnetic interference suppressor fillers with small particle size, medium particle size and large particle size respectively. S4. Preparation of three-layer insulation mixture: Maleimide-functionalized polyethylene, bis(2-methyl-3-furanyl) disulfide crosslinking agent, electromagnetic interference-resistant filler with corresponding particle size, maleic anhydride-modified nanofiber, antioxidant and compatibilizer are mixed in proportion to prepare the first, second and third insulation layer mixtures respectively. S5. Multi-layer co-extrusion coating molding adopts a three-layer co-extrusion process, in which the first, second and third insulation layer mixtures are melted and extruded from the inside to the outside, and coated on the surface of the core conductor. A composite insulation layer is formed through a cross-linking reaction. S6. Sheath extrusion: The sheath material is melted and extruded to cover the composite insulation layer, and then cooled and wound to obtain the finished cable.
10. The method for preparing the green and environmentally friendly flame-retardant medium-voltage cable according to claim 9, characterized in that, The copper catalyst in step S1 is cuprous iodide, the peroxide initiator is dicumyl peroxide, and the reaction temperature is 140-160℃; In step S3, the plasma treatment vacuum degree is 25-45 Pa, the glow discharge time is 3-5 min, the silane coupling agent mass concentration is 4%-8%, and the impregnation temperature is 45-65℃. In step S5, the extrusion temperature of the first insulating layer is 220-230℃, the extrusion temperature of the second insulating layer is 200-205℃, and the extrusion temperature of the third insulating layer is 175-180℃. After extrusion, hot-press crosslinking is carried out at 120-140℃ to complete the Diels-Alder reaction and permanent crosslinking.
